2011 13th International Conference on Transparent Optical Networks 2011
DOI: 10.1109/icton.2011.5970856
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to Augmented Reality with applications in aeronautical maintenance

Abstract: Augmented Reality is a breakthrough technology that could considerably ease execution of complex operations. Augmented Reality mixes virtual and actual reality, making available to the user new tools to ensure efficiency in the transfer of knowledge for several processes and in several environments. Various solutions based on Augmented Reality have been proposed by the research community: particularly in maintenance operations Augmented Reality tools have offered new perspectives and have promised dramatic imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 10 publications
0
40
0
2
Order By: Relevance
“…In addition, as Hincapie et al (2011) described, the information in traditional methods can be challenging to locate and extract. Indeed, workers and students -especially if inexperienced -can be led to frustration, poor performance, and potentially costly mistakes when trying to find information in traditional texts and manuals.…”
Section: Current Aviation Maintenance and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as Hincapie et al (2011) described, the information in traditional methods can be challenging to locate and extract. Indeed, workers and students -especially if inexperienced -can be led to frustration, poor performance, and potentially costly mistakes when trying to find information in traditional texts and manuals.…”
Section: Current Aviation Maintenance and Trainingmentioning
confidence: 99%
“…In aviation training and education, AR has been proven as a more effective learning tool than text or video-based methods (Macchiarella & Vincenzi, 2004), and could for instance help reduce training time and costs in maintenance, which typically amount to about 2000 hours (Hincapie et al, 2011). One project conducted by Ong, Yuan, and Nee, has demonstrated that AR is more effective than other forms of instructions, as it reduces errors and makes tasks easier (Ong, Yuan, & Nee, 2008).…”
Section: Potential Of Ar Aviation Maintenance and Trainingmentioning
confidence: 99%
“…Training specialized workers represents a considerable overhead in any business. As an example, it takes up to 2000 hours for aeronautic inspectors to complete their training [1]. This creates the need of human-centred assistance systems to support employees in their tasks, and help them to improve their skills.…”
Section: Introductionmentioning
confidence: 99%
“…AR glasses), although not that common, provide similar sensing capabilities with a higher level of immersion for the user. AR solutions have been used in different industries such as textile [2], aeronautic [1], medical care [3], manufactory [4] [5], military [6], and architectural construction [7] to support workers in their activities.…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance is one field where AR can play an important role [11], [12]. Maintenance tasks can be augmented using this technology, thus allowing the worker to carry wearable AR equipment instead of traditional heavy and difficult-to-use manuals.…”
Section: Introductionmentioning
confidence: 99%